Alterations of the lung methylome in allergic airway hyper‐responsiveness. (21st January 2014) - Cheng, Robert YS; Shang, Yan; Limjunyawong, Nathachit; Dao, Tyna; Das, Sandhya; Rabold, Richard; Sham, James SK; Mitzner, Wayne; Tang, Wan‐Yee; O'Hagan, Heather; Tang, Winnie
<x xml:space="preserve">Abstract</x> Asthma is a chronic airway disorder characterized by recurrent attacks of breathlessness and wheezing, affecting 300 million people around the world (available at: www.who.int). To date, genetic factors associated with asthma susceptibility have been unable to explain the full etiology of asthma. Recent studies have demonstrated that the epigenetic disruption of gene expression plays an equally important role in the development of asthma through interaction with our environment. We sensitized 6‐week‐old C57BL/6J mice with house‐dust‐mite (HDM) extracts intraperitoneally followed by 5 weeks of exposure to HDM challenges (three times a week) intratracheally. HDM‐exposed mice showed an increase in airway hyper‐responsiveness (AHR) and inflammation together with structural remodeling of the airways. We applied methylated DNA immunoprecipitation‐next generation sequencing (MeDIP‐seq) for profiling of DNA methylation changes in the lungs in response to HDM. We observed about 20 million reads by a single‐run of massive parallel sequencing. We performed bioinformatics and pathway analysis on the raw sequencing data to identify differentially methylated candidate genes in HDM‐exposed mice. Specifically, we have revealed that the transforming growth factor beta signaling pathway is epigenetically modulated by chronic exposure to HDM. Here, we demonstrated that a specific allergen may play a role in AHR through an epigenetic mechanism by disrupting the expression of genes in lungs that might be involved in airway inflammation and remodeling. Our findings provide new insights into the potential mechanisms by which environmental allergens induce allergic asthma and such insights may assist in the development of novel preventive and therapeutic options for this debilitative disease. Environ. Mol. Mutagen. 55:244–255, 2014. © 2014 Wiley Periodicals, Inc.